Resposta:
Letra B.
Explicação passo-a-passo[tex]Sen(c)= \frac{\frac{3x}{4} }{10} = \frac{3x}{40}\\Cos(c)=\frac{x}{10} \\tg(c)=\frac{\frac{3x}{4} }{x} = \frac{3x}{4x} = \frac{3}{4} = 0,75\\tg(c) = \frac{sen(c)}{cos(c)} => sen(c) = tg(c)*cos(c)\\sen^{2}(c)+cos^2(c)=1\\(tg(c)*cos(c))^2+cos^2(c)=1\\(\frac{3}{4} )^2*(\frac{x^2}{10^2})+ \frac{x^2}{10^2}=1\\ \frac{x^2}{10^2}(\frac{9}{16} +1) = 1\\ x^2 = \frac{100}{\frac{9}{16} +1} => x^2 = \frac{100}{\frac{9+16}{16}}\\x^2 = 64 = 8. \\cos(c) = 0,8 \\sen(c)=0,6.[/tex]